EFFECTIVENESS TEST OF INHIBITORY POWER OF LIME PEEL EXTRACT (Citrus aurantifolia) LIQUID SOAP AGAINST Staphylococcus epidermidis - Dessy Ratna Sari; Definingsih Yuliastuti; Firtania Philia Amnesti (Poltekkes Kemenkes Surakarta, 2025)
Lime peel (Citrus aurantifolia) is a horticultural waste whose utilization has not been optimal and contributes 50-65% of the residue of the total weight so that if lime peel is not utilized it can cause environmental pollution. Lime peel contains saponins, flavonoids, alkaloids, tannins, and essential oils that have inhibitory properties so that they can be utilized as a form of liquid soap preparation from lime peel extract. This study aims to determine the effectiveness of the inhibitory power of liquid soap preparations from lime peel extract (Citrus aurantifolia) containing essential oils as active substances against Staphylococcus epidermidis bacteria. This study used an experimental research method with a disc diffusion technique method that determined the inhibition zone. Liquid soap with lime peel essential oil 6% had effective inhibitory power against Staphylococcus epidermidis with an average diameter of the inhibition zone of 10.21 mm which is included in the strong category. The positive control and basic control resulted in an inhibition zone formed of 14.42 mm and 7,33 mm respectively. The effectiveness of strong inhibition was because essential oils contain phenol compounds that had hydrophobic properties by splitting the fat layer on the mitochondrial cell membrane and bacteria which causes cells to become damaged and results in extensive leakage in bacterial cells so that bacteria die. Data analysis using bivariate analysis with One Way Anova test showed that essential oils did not have a significant effect on the growth of Staphylococcus epidermidis bacteria compared to basic control.